1999
DOI: 10.1002/j.1551-8833.1999.tb08604.x
|View full text |Cite
|
Sign up to set email alerts
|

DBP formation potential of aquatic humic substances

Abstract: Terrestrial vegetation commonly shed into reservoirs contains chemical precursors of DBPs. Aquatic humic substances (AHSs) in water generate potentially harmful disinfection by‐products (DBPs) such as haloacetic acids (HAAs) and trihalomethanes (THMs) during chlorination. AHSs from two Arkansas reservoirs were characterized to define source, identify meta‐dihydroxybenzene (m‐DHB) structures as probable DBP precursors, and evaluate predicted HAA and THM formation potentials. Elemental nitrogen content < 1 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…The relatively low removal of DBP precursors and DOC through the biofilters was likely due to the absence of any pre-oxidation process such as ozonation (Chaiket et al, 2002;Siddiqui et al, 1997). Consistent with previous literature, humic substances, as measured using LC-OCD, were observed to be the primary precursors to DBP formation in Otonabee river water (Hubel and Edzwald, 1987;Pomes et al, 1999). Humic substance concentrations were also strongly correlated to the formation potential of AOX (R ¼ 0.95), THMs (R ¼ 0.96) and HAAs (R ¼ 0.96), whereas other organic fractions were not correlated to DBP formation (R < 0.7).…”
Section: Biofiltration Impacts On Regulated Disinfection By-products supporting
confidence: 83%
“…The relatively low removal of DBP precursors and DOC through the biofilters was likely due to the absence of any pre-oxidation process such as ozonation (Chaiket et al, 2002;Siddiqui et al, 1997). Consistent with previous literature, humic substances, as measured using LC-OCD, were observed to be the primary precursors to DBP formation in Otonabee river water (Hubel and Edzwald, 1987;Pomes et al, 1999). Humic substance concentrations were also strongly correlated to the formation potential of AOX (R ¼ 0.95), THMs (R ¼ 0.96) and HAAs (R ¼ 0.96), whereas other organic fractions were not correlated to DBP formation (R < 0.7).…”
Section: Biofiltration Impacts On Regulated Disinfection By-products supporting
confidence: 83%
“…Controlling the levels of THM precursors prior to chlorination should be deemed the most direct means of resolving THMs problems. Despite much research, the specific precursors involved in the formation of THMs are still not clear (Mallevialle et al 1990;Hureiki et al 1994;Pomes et al 1999). Moreover, recent studies have revealed that several aspects of the pipe environment may contribute to a more complex reaction system.…”
Section: Introductionmentioning
confidence: 95%
“…Absorbance was measured at 254 nm, 280 nm (E 2 wavelength), 350 nm (E 3 wavelength), 400 nm, 436 nm, 465 nm (E 4 wavelength) and 665 nm (E 6 wavelength); consistent with previous studies of THMFP using UV-visible absorbance measurements [8,13,18,19]. The absorbance measured at 465 nm was divided by the absorbance measured at 665 nm to give the E 4 to E 6 ratio, whereas the ratio of the absorbance at 280 nm to the absorbance at 350 nm yielded E 2 /E 3 .…”
Section: Uv-visible Absorption Measurementsmentioning
confidence: 98%
“…Although the THMFP has not been measured for the LFA because it is a soil-derived humic substance, the spectral results obtained for this material are included for comparison with the other humic substances. The absorbance values at 350, 400, 436, 465 and 665 nm arise from the chromophoric groups containing conjugated double bonds and heteroatoms with lone pairs of electrons like O, N and S. The absorption at 400 nm is a surrogate used for color and a correlation between THMFP and color has been reported [8,18]. Absorbance was also measured at 254 and 280 nm because these wavelengths are known to represent the aromatic content of humic substances [8,18,21,22].…”
Section: Uv-visible Absorption Spectramentioning
confidence: 99%
See 1 more Smart Citation